2021
DOI: 10.1038/s41598-021-92599-w
|View full text |Cite
|
Sign up to set email alerts
|

Combination of retinoids and narrow-band ultraviolet B inhibits matrix metalloproteinase 13 expression in HaCaT keratinocytes and a mouse model of psoriasis

Abstract: Matrix metalloproteinase13 (MMP13) can be released by keratinocytes and fibroblasts and involved in the pathogenesis of skin disorders. Retinoic acid derivative drugs include tazarotene and acitretin. Tazarotene/acitretin and narrow-band ultraviolet B (NB-UVB) irradiation are common treatment options for psoriasis. However, their impact on MMP13 expression in the context of psoriasis has yet to be determined. The expression of MMP13 was analyzed in patients with psoriasis. The effects of tazarotene/acitretin a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
(22 reference statements)
0
5
0
Order By: Relevance
“…Since elevated levels of particularly MMP-2, MMP-8, and MMP-9, have been observed in HS lesions, we have chosen to focus on these specific isoforms [74], [75], [118], [119]. Similar trends regarding elevated levels of specific MMPs are observed in psoriasis skin [120]- [123]. MMPs are activated as part of the inflammatory immune response, meaning that these targets are prominent in the later stages of HS.…”
Section: Target 2: Matrix Metalloproteinasesmentioning
confidence: 98%
See 1 more Smart Citation
“…Since elevated levels of particularly MMP-2, MMP-8, and MMP-9, have been observed in HS lesions, we have chosen to focus on these specific isoforms [74], [75], [118], [119]. Similar trends regarding elevated levels of specific MMPs are observed in psoriasis skin [120]- [123]. MMPs are activated as part of the inflammatory immune response, meaning that these targets are prominent in the later stages of HS.…”
Section: Target 2: Matrix Metalloproteinasesmentioning
confidence: 98%
“…Dysregulation and overexpression of MMP-9 seems to be associated with some diseases, thus emphasizing the importance of examining its inhibition and regulation, in relation to HS. Due to the structural similarities between MMP-2 and MMP-9, the inhibition of MMP-9 is also likely to result in the inhibition of MMP-2 and vice versa [123], [129].…”
Section: Target 2: Matrix Metalloproteinasesmentioning
confidence: 99%
“…The success rates of treatment and onset of action were greater with larger dose but a decrease in lesions on trunk, limb, knee and elbow was observed with both doses. The response lasted for twelve weeks in 50% of patients after treatment with no reports of tachyphylaxis even after 1 year 41,42 . Xi et al, 2021, found an increased level of MMP13 in the samples of skin lesions and serum from the patients with psoriasis.…”
Section: In Psoriasismentioning
confidence: 98%
“…It was approved to be used as cream (0.05 and 0.1%) in US for psoriasis in September 2000, and 0.1% for acne vulgaris in October 2001. 0.1% TZR cream was approved as an adjuvant to other topical retinoids to reduce the signs of facial photodamage in September 2002 42 .…”
Section: Regulatory Affairsmentioning
confidence: 99%
See 1 more Smart Citation